2009
DOI: 10.1055/s-0029-1192034
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl Ester Transfer Protein I405V Polymorphism Influences Apolipoprotein A-I Response to a Change in Dietary Fatty Acid Composition

Abstract: The aim of the present study was to investigate whether the cholesteryl ester transfer protein (CETP) I405V polymorphism modifies the response to changes in the dietary ratio of polyunsaturated to saturated fat (P:S). The population included 85 healthy subjects with the different I405V genotypes (35 II, 36 IV, and 14 VV) assigned to two consecutive 28-day experimental period. All subjects consumed a high-P:S with P:S of 1.2 for the first period and a low-P:S with a P:S of 0.3 for the next 28-day period. At the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Most studies included both sexes, but two studies assessed CETP gene and diet interaction only in male subjects [ 23 , 42 ]. These studies were conducted in several different countries, including New Zealand [ 23 , 26 , 39 , 41 ], Israel [ 6 , 22 ], the United States [ 7 , 38 , 42 , 49 ], Europe [ 30 , 33 , 35 , 40 , 46 48 , 50 ], China [ 34 , 51 ], Brazil [ 43 , 44 ], Japan [ 21 ], Iran [ 36 ], and Canada [ 37 , 45 ]. The studies examined the effects of the following individual or combinations of polymorphisms: Taq1B (17 studies), I405V (7 studies), rs3764261 (2 studies), C > T/In9 (one study), and rs183130 (1 study).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies included both sexes, but two studies assessed CETP gene and diet interaction only in male subjects [ 23 , 42 ]. These studies were conducted in several different countries, including New Zealand [ 23 , 26 , 39 , 41 ], Israel [ 6 , 22 ], the United States [ 7 , 38 , 42 , 49 ], Europe [ 30 , 33 , 35 , 40 , 46 48 , 50 ], China [ 34 , 51 ], Brazil [ 43 , 44 ], Japan [ 21 ], Iran [ 36 ], and Canada [ 37 , 45 ]. The studies examined the effects of the following individual or combinations of polymorphisms: Taq1B (17 studies), I405V (7 studies), rs3764261 (2 studies), C > T/In9 (one study), and rs183130 (1 study).…”
Section: Resultsmentioning
confidence: 99%
“…The altered expression of cat (catalase) is associated with oxidative DNA damage and subsequent cancer susceptibility [92], [93]. Cetp (Cholesteryl ester transfer protein), also called plasma lipid transfer protein [94], [95] and Abca1 (ATP-binding cassette transporter sub-family) are major regulators of cellular cholesterol and phospholipid homeostasis. Abca1functions as a cholesterol efflux pump in the cellular lipid removal pathway [96].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, carriers of the I405V (rs5882) polymorphism in the CETP gene had higher plasma TC levels when consuming a high-TotFat diet. Previously, Darabi et al ( 38 ) showed that subjects carrying the mutated allele had a greater reduction in plasma HDL-C levels without changes in TC compared with subjects with the other genotype after a diet low in PUFA:SatFat ratio ( 38 ) . Thus, these genetic variations may modulate the effect of dietary fat on blood lipids in the Inuit and other populations; yet, more studies are needed to validate these gene–diet interaction effects.…”
Section: Discussionmentioning
confidence: 99%